Influence of an uneven surface on the vibration occurrence affecting the tractor operator - Barač, Željko; Plaščak, Ivan; Jurić, Tomislav, agronom; Baličević, Pavo; Duvnjak, Vinko; Jurišić, Mladen; Heffer, Goran; Marković, Monika (2019)
The paper presents a study of the influence of an uneven surface and number of tractor hours on vibration that is transmitted to the operator's hand-arm system during operation. The study was conducted on the asphalt, gravel and grass traversal during 2015 and 2016. The results indicate that the movement of a tractor on different agrotechnical surfaces generates vibrations of varying intensity that affect the hand-arm system of the operator. The highest vibration values were recorded on the asphalt, while the least vibrations were measured on the grass. The measured maximum vibration values are lower than the permissible 5 m·s−2 in the direction of all three axes, making it possible to assume that they are not harmful to the health of the operator.
Bibliografija: 24 jed.
Abstract.
Keywords: Poljoprivredna mehanizacija -- Traktori -- Vozači traktora -- Vibracije -- Agrotehničke površine -- Zaštita na radu